The Influence of Eugenol in Lubrication Properties of Crude Jatropha Curcas Lin - Ma’arif, Moch. Syamsul; I.N.G. Wardana; Djarot B. Darmadi; Oyong Novareza; Zainal Abidin; Erwin Sulistyo; Cahyo Henan Darsono (International Journal of Integrated Engineering, 2024)
In machining processes, vegetable oil based lubricant has very promising future to substitute petroleum based lubricant. Due to sustainability issue, lubricants from natural resources is sought after as complement or even substitute for non renewable lubricants. Jatropha curcas Lin oil (JCO) is one of such natural oil. When tested as lubricant, JCO demonstrates good performance and decomposition properties. The research on JCO usually study the performance the oil by characterizing of friction reduced parameters and rarely to analyze deeper in terms of the role of molecular interaction between components of vegetable oil and metal surfaces. To analyses the moleculer interaction, a commercially available software for molecular interaction simulation is employed. In order to simulate the interactions, the procedure of simulation are firstly construct molecular model of JCO components. The model then is employed as basis for the software to calculate interactive forces of each atom or molecule with the neighboring one thru their positions. From the simulation results, it was concluded that value of Dipole Moment, Polarisability, and Bond Energy of Jatropha oil compound decreased when the concentration of Eugenol is increasing. The conclusion is hold true up to 20% of eugenol additon